Reiterating the Canadian West: Introduction. (February 2016) - Rusted, Brian
Contemporary discussions of the Canadian West tend to differentiate it as a geographic space from American practices south of the border, or from Hollywood imaginaries. Such discussions are often developed through comparison: in terms of demography, representation, class, and political economy, or they conclude that national boundaries do not reflect cultural differences. Increasingly, research on the Canadian West troubles geographic understandings of place and imposed settler classifications and categories. The articles in this issue advance this arc to engage sensory, embodied, and more-than-representational features that reiterate multiple Wests. Through critically engaged methods of writing about archival ephemera, narratives and song, festive and tourist experiences, and popular media and illustration, these articles contribute to understanding the Canadian West as practiced and performed.